Open-book accounting no relacionamento entre comprador e fornecedor no setor agroindustrial - Cardoso, Anderson Martins (2019)
Business organizations are increasingly urged to work in a balanced way on aspects of economic efficiency in interorganizational relationships, seeking to optimize processes, eliminate waste, reduce costs and generate value, in order to present more advantageous results in a highly competitive environment. This context favors the use of collaborative approaches to cost management such as Interorganizational Cost Management (IOCM) and the practice of Open-Book Accounting (OBA). In this sense, the objective of this research was to identify how the OBA is practiced in the relationship between an agroindustrial company and one of its direct suppliers, from the TCE perspective. Methodologically, this is a unique case study, dyad approach, developed with an agroindustry buying company and one of its direct suppliers. For data collection, semi-structured interviews, document analysis and direct observation were used. Data analysis was performed through Content Analysis. The results evidenced that the OBA is applied bilaterally, with a high level of detailing information by the supplier, and eventually and at a low level of detail from the buyer. It was found that the OBA was not a practice since the beginning of the relationship and therefore was not imposed by the buyer. The process of sharing information through the OBA emerged from the moment the trust was established, which required time of relationship and commitment of the parts in the application of the "win-win" principle, with the opportunity to expand joint ventures and with an exclusively "very long-term" supply contract, thus reducing the risk of opportunistic behavior by the parts. It was verified, therefore, that trust was a prerequisite for the application of the OBA and that, from the more open sharing of information, there was an increase of benefits for both companies. Another finding relates to the fact that OBA is not applied in order to manage costs in the chain, but rather to support another tool, Total Cost of Ownership (TCO), mainly used for selection, negotiation and renegotiation with suppliers, and not necessarily for interorganizational cost management. With this, it was verified that there is development of joint activities, however these are punctual and eventual, like the use of the Value Engineering technique. Additionally, the results evidenced that the formal contract is the main safeguard of the relationship, although there are also relational safeguards, such as trust, which was perceived as partial. Finally, it was observed that the investment in specific assets by the supplier increased the bilateral dependence of the parts and the interest in establishing a contract of longer duration in order to minimize the risks involved in the relationship of both the purchasing company, which depends of the continuous supply of the product that integrates its production process, and of the supplier, who depends on the guarantee of a high volume of purchase of the supplied product, that justifies economically the investment made. It is concluded, therefore, that the consensual sharing of information, with predictions of mutual benefits, increases the willingness to use the OBA and, consequently, increases the chances of identifying opportunities for cost reduction; that OBA is not used for its primary purpose of managing costs in the supply chain; and that there is a need for more empirical research on the subject to understand the gaps between what literature and theory predict and what actually occurs in practice.